Oxidative balance score and oxidative stress biomarkers in a study of Whites, African Americans, and African immigrants. (September 2014) - Lakkur, Sindhu; Bostick, Roberd M.; Roblin, Douglas; Ndirangu, Murugi; Okosun, Ike; Annor, Francis; Judd, Suzanne; Dana Flanders, W.; Stevens, Victoria L.; Goodman, Michael
Abstract Context: Oxidative balance score (OBS) is a composite measure of multiple pro- and antioxidant exposures. Objective: To investigate associations of OBS with F2-isoprostanes (FIP), mitochondrial DNA copy number (mtDNA), and fluorescent oxidative products (FOP), and assess inter-relationships among the biomarkers. Methods: In a cross-sectional study, associations of a thirteen-component OBS with biomarker levels were assessed using multivariable regression models. Results: Association of OBS with FIP, but not with FOP, was in the hypothesized direction. The results for mtDNA were unstable and analysis-dependent. The three biomarkers were not inter-correlated. Conclusions: Different biomarkers of oxidative stress may reflect different biological processes.